2001
DOI: 10.3109/10428190109064603
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Notchl and Jaggedl Proteins in Acute Myeloid Leukemia Cells

Abstract: Cell fate of hematopoietic progenitors is regulated by interaction between Notch proteins on progenitors and Notch ligands such as Jagged1 on stromal cells. Since acute myeloid leukemia (AML) originates from dysregulated hematopoietic progenitors, some abnormalities in the Notch-Jagged system may exist in AML cells. As the first step to clarify this, we examined the expression of Notch1 and Jagged1 proteins in eight AML cell lines and 15 fresh AML samples by immunoblotting. In the Notch1 protein, two bands, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
68
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 16 publications
6
68
0
Order By: Relevance
“…Deregulated expression of wild-type Notch or of Notch ligands or downstream targets has been detected in cervical, lung, colon, head and neck, and renal carcinomas (54 -57), acute myeloid leukemia (58), and Hodgkin's and large cell lymphomas (59). Notch1 was recently shown to be a downstream effector of oncogenic Ras, and down-regulation of Notch1 in Ras-transformed human cells was sufficient to abolish key elements of the neoplastic phenotype in vitro and in vivo (60).…”
Section: Discussionmentioning
confidence: 99%
“…Deregulated expression of wild-type Notch or of Notch ligands or downstream targets has been detected in cervical, lung, colon, head and neck, and renal carcinomas (54 -57), acute myeloid leukemia (58), and Hodgkin's and large cell lymphomas (59). Notch1 was recently shown to be a downstream effector of oncogenic Ras, and down-regulation of Notch1 in Ras-transformed human cells was sufficient to abolish key elements of the neoplastic phenotype in vitro and in vivo (60).…”
Section: Discussionmentioning
confidence: 99%
“…Loss or mutation of p53 is common in many types of human cancer, including a mutation rate of 13% in lymphoid malignancies (reviewed in [3]). A variety of studies have also linked cell survival and, potentially, cancer development with Notch expression [42][43][44][45][46][47][48][49][50], (reviewed in [9]). The Trp53 -/-mice develop tumors, primarily lymphomas, by approximately 4 months of age [4], which may partially be due to the increased N IC expression observed in Trp53 -/-thymocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that constitutive overexpression of active Notch-1, -2 or -3 predisposes to T-cell malignancies (Aster and Pear, 2001). Among hematopoietic malignancies, acute myeloid leukemia (Tohda and Nara, 2001) as well as Hodgkin and largecell anaplastic lymphomas (Jundt et al, 2002) have been shown to overexpress Notch-1, while B-cell CLL has been shown to overexpress Notch-2 (Hubmann et al, 2002). Moreover, Jagged-1/Notch-1 interactions have been shown to induce proliferation and survival in Hodgkin and large-cell anaplastic lymphomas (Jundt et al, 2002).…”
Section: Introductionmentioning
confidence: 99%